Latent Alcohol Use Typologies and Health Status Among a Cohort of Adults Living with HIV. (3rd October 2019) - Madkour, Aubrey Spriggs; Felker-Kantor, Erica; Wallace, Maeve; Ferguson, Tekeda; Welsh, David A; Molina, Patricia E; Theall, Katherine P
Abstract: Aims: To characterize latent typologies of alcohol use among persons living with human immunodeficiency virus (HIV) (PLWH) and test their relationship with physical and mental health status. Methods: Baseline data from 365 adult in-care PLWH enrolled in the New Orleans Alcohol Use in HIV study were analyzed. Indicators of current and former heavy drinking, intoxication, withdrawal and dependence symptoms, alcohol-related problems and past contact with alcohol use treatment were drawn from validated scales. Physical and mental health measures included SF-36 subscales, medication non-adherence and anxiety, depressive and post-traumatic stress disorder symptoms. Latent class analysis was conducted to characterize alcohol drinking typologies. Logistic and ordinary least-squares regression were employed to test associations between alcohol use and health status. Results: Four latent classes were identified: heavy drinkers (36%), former heavy drinkers (14%), heavy drinkers with problems (12%) and low-risk drinkers/abstainers (38%). Controlling for background characteristics, low-risk drinkers/abstainers showed significantly better health compared to heavy drinkers with problems across most domains. Although current and former heavy drinkers without alcohol-related problems were similar to heavy drinkers with problems in most health domains, they presented worse mental health and energy compared to low-risk drinkers/abstainers. Conclusions: Heavy drinkers with alcohol-related problems evidenced the worst health status among PLWH, and should be considered for mental and physical health interventions. However, interventions to improve physical and mental health of PLWH should consider history of heavy alcohol use, as current alcohol use status alone may be insufficient for identifying groups at increased risk. Abstract : In a cohort of adult PLWH, four classes of alcohol use were identified: heavy drinkers, former heavy drinkers, heavy drinkers with problems and low risk drinkers/abstainers. Heavy drinkers with problems presented the worst health status, and former heavy drinkers and heavy drinkers experienced worse mental health than low-risk drinkers/abstainers.